Intus legere: o método qualitativo fenomenológico em pesquisa teológica = Intus legere: the phenomenological qualitative method in theological research = Intus legere: el método cualitativo fenomenológico en la investigación teológica - Teixeira, Patrícia Espíndola de Lima (Teocomunicação, 2023)
The article has a descriptive character and intends to contribute toresearch in the theological area, expanding the possibilities of qualitative methods. The word method comes from the Greek methodos, which means to followthe path to an end. The term indicates a scientific investigation, delineated, andsystematized with the objective of producing new knowledges, discussing and/or integrating with existing ones. It can be seen that in research at the strictosensu level, instruments of data collection through empirical studies are frequent in the field of Human Sciences, but not always common in the theologicalfield. Among the existing powerful qualitative methods, the article addressesphenomenological investigation in its epistemology and exemplifies the workof the author in her doctoral thesis. It describes the phenomenological methodthrough intus legere experience, which indicates reading from within humanexperiences. It explains the development of narrative interviews and details theexploration and systematization of the findings by means of discursive textualanalysis as coherent with the phenomenological attitude. The article presents asa digital tool resource, the ATLAS.ti software. It is an optimizing support for qualitative research. It concludes by emphasizing that the complexity of theologicalcontemporaneity is abundant in possibilities of original scientific elaborationsby expanding in empirical research the theoretical foundations, especially withdigital technological facilitators. It concludes by encouraging new researchersin the theological field to develop the novelty of their authorships in the courseof qualitative phenomenological research.